pengaruh efikasi diri dan kemandirian belajar peserta didik terhadap prestasi belajar kimia kelas X SMA Negeri 15 Pekanbaru - Rahmawati, Ayu; Anwar, Lenny; Rasmiwetti, Rasmiwetti; Nursofia, Yesi (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2024)
Self-efficacy and learning independence are important factors in improving chemistry learning achievement and these factors must be mastered by students. This study aims to determine the effect of self-efficacy and learning independence on chemistry learning achievement partially or simultaneously. This type of research is a survey-research with a quantitative approach. The data collection methods for this study are questionnaires and documentation. The self-efficacy and learning independence questionnaires used were 21 questions after being validated. The questionnaires were distributed to all samples of 119 students taken using the simple random sampling technique. Documentation was used to collect data on chemistry learning achievement scores. Data analysis used in this study was multiple linear regression analysis. The results of the study showed (1) There is a positive and significant effect of self-efficacy partially on chemistry learning achievement, (2) there is a positive and significant effect of learning independence on learning achievement, (3) There is a positive and significant effect between self-efficacy and learning independence simultaneously on chemistry learning achievement.